2018
DOI: 10.3126/jnps.v37i2.17124
|View full text |Cite
|
Sign up to set email alerts
|

Children with Cerebral Palsy and their Quality Of Life in Nepal

Abstract: Introduction: Cerebral Palsy (CP) may affect individual's everyday life and it may have significant impact on quality of life (QOL). The objective of this study was to assess the quality of life of children with Cerebral Palsy in Nepal. Material and Methods: This is a descriptive cross sectional study that involved 42 children between 4 and 12 years of age. The Socio-demographic variables were obtained from interviews and CP related factors were obtained from medical reports. Validated CP-QOL child self-report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
1
0
2
Order By: Relevance
“…Physical independence, mobility, and social integration dimensions were more severely affected by the clinical burden, economic burden, and educational factors (Dobhal, Juneja, Jain, Sairam, & Thiagarajan, 2014). In contrast, a study conducted by Shrestha, Paudel, & Thapa (2017) in Nepal suggested that QOL is quite good in children with CP, in terms of children's psychosocial conditions; however, the physical attributes were still poor or low in QOL. The QOL of children with CP in Indonesia varies.…”
Section: Introductionmentioning
confidence: 93%
“…Physical independence, mobility, and social integration dimensions were more severely affected by the clinical burden, economic burden, and educational factors (Dobhal, Juneja, Jain, Sairam, & Thiagarajan, 2014). In contrast, a study conducted by Shrestha, Paudel, & Thapa (2017) in Nepal suggested that QOL is quite good in children with CP, in terms of children's psychosocial conditions; however, the physical attributes were still poor or low in QOL. The QOL of children with CP in Indonesia varies.…”
Section: Introductionmentioning
confidence: 93%
“…Informasi ini penting dalam pengambilan keputusan klinis. 8 Tujuan dari penelitian ini adalah untuk mengetahui apakah ada hubungan (korelasi) antara tingkat spastisitas pergelangan kaki terhadap kualitas hidup anak dengan CP tipe spastik quadriplegia.…”
Section: Pendahuluanunclassified
“…Skor terendah ada pada domain rasa sakit dan dampak dari kecacatan. 8 Terdapat korelasi (negatif) signifikan yang sangat kuat antara tingkat spastisitas pergelangan kaki terhadap kualitas hidup anak dengan CP tipe spastik quadriplegia pada domain penerimaan dan kesejahteraan sosial (p: 0.000; CC: 0.87); perasaan mengenai fungsi (p: 0.000; CC: 0.86); partisipasi dan kesehatan fisik (p: 0.000; CC: 0.85); kesejahteraan emosional dan kepercayaan diri (p: 0.000; CC: 0.86). Terdapat korelasi (negatif) signifikan yang kuat pada domain rasa sakit dan dampak dari disabilitas (p: 0.002; CC: 0.65).…”
Section: Pembahasanunclassified